Genetic variation in horizontally transmitted fungal endophytes of pine needles reveals population structure in cryptic species1. Issue 8 (1st August 2014) - Oono, Ryoko; Lutzoni, François; Arnold, A. Elizabeth; Kaye, Laurel; U'Ren, Jana M.; May, Georgiana; Carbone, Ignazio
Abstract : Premise of the study: Fungal endophytes comprise one of the most ubiquitous groups of plant symbionts, inhabiting healthy leaves and stems of all major lineages of plants. Together, they comprise immense species richness, but little is known about the fundamental processes that generate their diversity. Exploration of their population structure is needed, especially with regard to geographic distributions and host affiliations. Methods: We take a multilocus approach to examine genetic variation within and among populations of Lophodermium australe, an endophytic fungus commonly associated with healthy foliage of pines in the southeastern United States. Sampling focused on two pine species ranging from montane to coastal regions of North Carolina and Virginia. Key results: Our sampling revealed two genetically distinct groups within Lophodermium australe . Our analysis detected less than one migrant per generation between them, indicating that they are distinct species. The species comprising the majority of isolates ( major species) demonstrated a panmictic structure, whereas the species comprising the minority of isolates ( cryptic species) demonstrated isolation by distance. Distantly related pine species hosted the same Lophodermium species, and host species did not influence genetic structure. Conclusions: We present the first evidence for isolation by distance in a foliar fungal endophyte that is horizontally transmitted. Cryptic species may be common among microbial symbionts and are important to delimit when exploring their genetic structure and microevolutionary processes. The hyperdiversity of endophytic fungi may be explained in part by cryptic species without apparent ecological and morphological differences as well as genetic diversification within rare fungal species across large spatial scales.